KETAHANAN ALAMI BEBERAPA GENOTIPE CABAI (Capsicum annuum L.) TERHADAP PENYAKIT ANTRAKNOSA - Suryotomo, Bambang (Jurnal Sains dan Teknologi Indonesia, 2006)
The objective of this reseach was evaluated the Resistance of four Hot pepper to antracnose on pre harvested and (2) evaluated the best method to needed inoculated of the resistance antracnose and (3) to findthe superior genotipe of resistance antracnose. The research was conducted in the Greenhouse of the Departement of agronomy and Laboratory of the Departement of Plant Pest and Disease, Faculty of Agriculture, Bogor Agriculture University, until 12 mount. Resistance evaluation evaluation on pre-harvesting fruits was done in the Greenhouse with “spray” inoculation method of 106 spore/ml Colletotrichum gloeosporioides suspension at flowering stage and fruit-set stage. The research were set in a Factorial and Completely Randomized Design with four replication and five plants per experimental unit. The genotipes evaluated were UPM, Tit Super, Yogya and Jatilaba. Observations were done on disease sevarity, disease incidence and percentage fruit damage. The results showed that resistance level of all genotypes were lower when inoculated at fruit-set stage compared to at flowering stage. The best method of evaluation for resistance to antracnose on hot pepper was the Greenhouse test inoculation at fruit-set stage with variable of disease incidence. All genotipes tested were considered very susceptible to Colletotrichum gloeosporioides (Antracnose).